ASSESSMENT OF GEOMETRIC CONSISTENCY OF THE NIGERIAN ADMINISTRATIVE BOUNDARIES DATASETS FROM DIFFERENT SOURCES: THE NEED FOR DATA HARMONY AND STANDARDIZATION - Adaviruku, Peter Emmanjay (FUDMA Journal of Sciences, 2025)
Precise administrative boundaries demarcation facilitates effective governance, policy making, resource allocation and the delivery of public services. The delineation of administrative boundaries in Nigeria has been an ongoing challenge, with several disputes and boundary adjustments over the years. Different sources of datasets on Nigerian administrative boundaries exhibit inconsistencies, leading to discrepancies and misalignment. The aim of this study therefore is to assess the geometric consistency of the Nigerian administrative boundaries datasets from different sources. The datasets were sourced from the Office of Surveyor General of Federation (OSGoF), Geo-Referenced Infrastructure and Demographic Data for Development (GRID3), Global Administrative Areas (GADM) and Divas GIS. These datasets were analyzed in ArcGIS 10.8 for alignment and discrepancy. The findings revealed that the Global Administrative Areas datasets showed general good alignment for the Nigerian national boundary. On the contrary, the datasets from GRID3 and Divas GIS have gross misalignment. Furthermore, the misalignment observed in the datasets is generally prominent in the eastern part where Nigeria shares border with Cameroon. Significant discrepancies were observed between the datasets at all level of boundaries from the various sources compared. The result also revealed that the Nigerian national boundary from the Office of Surveyor General of Federation is 912,153.24 km2 in area, while datasets from Divas GIS is -1,991.09 km2 (-0.22%) smaller, GADM is -1,991.09 km2 (-0.22%) lower and GRID3 is 2,330.75 km2 (0.26%) higher than OSGoF dataset. The study therefore concluded that these discrepancies could have a significant impact on spatial analysis, resource allocation, and decision-making processes.
Keywords: Administrative boundary; Geometric consistency; Data alignment; Boundary demarcation